Peran Kegiatan Paskibra dalam Pembentukan Jiwa Kepemimpinan Santri Kelas 10 Ma’had Al Zaytun - Murningsih, Sri; Sobirin; Abdurrozaq, Muhammad; Suryandari, Meity (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Paskibra (Flag-Raising Troop) program at Ma'had Al-Zaytun serves as a character development activity aimed at fostering discipline, responsibility, mental resilience, and leadership among tenth-grade Madrasah Aliyah (MA) students. The program focuses not only on marching drills and flag-raising ceremonies but also on instilling the values of teamwork, courage, communication, and leadership skills applicable to both daily life and organizational settings. This study aims to examine the role of the Paskibra program in developing the leadership qualities of tenth-grade MA students at Ma'had Al-Zaytun and to identify the supporting and inhibiting factors influencing this process. The research employed a descriptive qualitative method with a field research approach. Data were collected through observations, interviews, and documentation involving instructors, teachers, alumni, and tenth-grade MA students. The collected data were analyzed inductively through the stages of data reduction, data presentation, and conclusion drawing. The findings indicate that active participation in the Paskibra program contributes significantly to the development of students' leadership character. Continuous training enhances discipline, responsibility, communication skills, teamwork, courage, assertiveness, and self-confidence, thereby preparing students to become effective leaders for themselves and others (Rahmawati, 2021; Prasetyo, 2023; Suciati, 2024). The success of this character-building process is supported by regular training routines, guidance from instructors, and the delegation of responsibilities to students. However, the program still faces challenges, including low self-confidence among some participants and the diversity of members' personalities and backgrounds. Therefore, continuous and sustainable coaching is essential to optimize the development of students' leadership qualities.